Survey analysis to determine the impact of evidence informed practice education upon East Asian medicine faculty clinical instruction and students’ skills, knowledge, attitudes and behaviors within a master’s degree program - Anderson, Belinda J. (BMC Med Educ, 2021)
BACKGROUND: Between 2013 and 2018 Pacific College of Health and Science (formerly Pacific College of Oriental Medicine) trained faculty and developed curriculum in evidence informed practice (EIP), with support from a grant from the National Institutes of Health (NIH). A three-credit (45 h) Foundations of EIP course, and online EIP learning modules (developed as part of a previous NIH R25 award), were used for faculty and student training. In addition, EIP was incorporated into 73% of the East Asian medicine degree program. Clinical integration of EIP in the College clinic was enhanced by improving access to reference sources, including additional EIP-related questions to the patient intake forms, requiring the use of a patient-centered outcome instrument, and assessing students’ clinical EIP competencies. METHODS: Master’s degree students’ self-reported EIP skills, knowledge, attitudes and behaviors were assessed before and after taking the Foundations of EIP course using a 17-question paper-based survey with an additional open-ended comments section. The survey was administered in 29 courses across all three Pacific College campuses. Clinical faculty self-reported EIP instruction, focusing on the EIP content and instructional approaches that were utilized, was evaluated on the New York City campus using a paper-based survey before and after changes were made to enhance the clinical integration of EIP. RESULTS: A total of 1181 completed EIP-course surveys consisting of 657 pre-EIP course surveys and 524 post-EIP course surveys were analyzed. There was a statistically significant improvement in students’ EIP skills, knowledge and behaviors after completing the EIP course. Students’ perception of the importance of EIP was high before and after the EIP course. Little change in Faculty’s EIP-related clinical instruction was evident following the EIP-related changes that were made to the Clinic. CONCLUSION: Our study suggests that the three-credit (45 h) EIP course was effective at improving the EIP skills, knowledge and behaviors of this group of East Asian medicine students who were undertaking a master’s degree that qualified them for licensure in acupuncture in the US. These students also demonstrated a high level of recognition for the importance of research and EIP both before and after the course. Training faculty clinical supervisors and providing greater access to evidence sources in the College clinic did not appear to increase EIP instructional activity.